2017
DOI: 10.1182/blood-2016-11-693689
|View full text |Cite
|
Sign up to set email alerts
|

How I treat autoimmune hemolytic anemia

Abstract: Autoimmune hemolytic anemia (AIHA) is an uncommon entity that presents diagnostic, prognostic, and therapeutic dilemmas despite being a well-recognized entity for over 150 years. This is because of significant differences in the rates of hemolysis and associated diseases and because there is considerable clinical heterogeneity. In addition, there is a lack of clinical trials required to refine and update standardized and evidence-based therapeutic approaches. To aid the clinician in AIHA management, we present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
116
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(125 citation statements)
references
References 81 publications
(70 reference statements)
5
116
0
4
Order By: Relevance
“…However, fewer than 20% of patients have a long-term response to corticosteroid therapy alone [4]. The recommended second-line therapy is splenectomy or rituximab [5, 6]. Rituximab is favored over splenectomy in patients with secondary WAIHA due to the low response rates to splenectomy in this patient population [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, fewer than 20% of patients have a long-term response to corticosteroid therapy alone [4]. The recommended second-line therapy is splenectomy or rituximab [5, 6]. Rituximab is favored over splenectomy in patients with secondary WAIHA due to the low response rates to splenectomy in this patient population [7].…”
Section: Introductionmentioning
confidence: 99%
“…Autoimmune haemolytic anaemia (AIHA) is a heterogeneous group of diseases characterized by autoantibody production to red cell antigens causing shortened survival of the red cells. Anaemia caused by red blood cell (RBC) autoantibodies is not common [1]. In 1946 it was observed that the red cells of patients with acquired haemolytic anaemia sometimes had a positive direct antiglobulin test (DAT) but patients with hereditary haemolytic anaemias were DAT negative and this led to the discovery of AIHA due to the development of autoantibody to the red cells [2].…”
Section: Introductionmentioning
confidence: 99%
“…AIHA has an incidence of 1-3 cases per 100,000/year [1]. More than half the cases of AIHA are warm AIHA with an incidence of 1/50,000 -80,000 persons [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Presence of cold agglutinin in this case was clinically significant leading to gangrene with subsequent amputation. Treatment of WAIHA includes steroids with or without rituximab and or splenectomy with anticipated response in 80% of patients while treatment of CAD is more challenging . The treatment of mixed‐type AIHA is less well defined because of its rarity.…”
mentioning
confidence: 99%